Penguatan Manajemen BUMDES untuk Peningkatan Kesejahteraan Masyarakat Di Kecamatan Rasau Jaya - Hardilina; Azrita Mardhalena; Indah Sulisdiani; Hairil Anwar; Nahot Tua Parlindungan Sihaloho (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The ifield iorientation iin iRasau iJaya iDistrict, iKubu iRaya iCity, ifound iindications ithat ithe Management iof iVillage iOwned iEnterprises i(BUMDes) iin ipromoting icommunity iwelfare ithrough the ibusiness iunit ibuilt iby iBUMDes iin iRasau iJaya iVillage iis istill ifar ifrom iexpectations. iThis is ibecause ithe iunderstanding iof ithe iVillage iHead iregarding ithe irespective iBUMDes iis ivery lacking. iWeak iunderstanding iof iBUMDes iis iwhat imakes iBUMDes idiscourse inot iwell isocialized to ivillagers. iSo ithat ithe igrowth iand idevelopment iof iBUMDes ias ia isupport ifor ithe ivillage economy ihas inot ibeen ifelt ioptimally iby ithe icommunity. iThe imethod iof iimplementing iPKM activities iis iin ithe iform iof icounseling: iSocialization idelivered iby iresource ipersons iregarding BUMDes imanagement istrategies iin iplanning, iorganizing, imarketing istrategies iand ipromoting BumDes ibusiness iproducts, ias iwell ias iselecting iopportunities ior ibusiness iunits ithrough ivillage potential. iThe ievaluation iof ithe iprogram ioffered iby ithe iPKM iFISIP iTeam iat iTanjungpura University irequires ithe icooperation iof ivarious iparties iin isupporting ivillage ieconomic development ithrough ithe imanagement iof iBUMDes, inamely iby iproviding ivillage iassistance, especially ifrom ivillage iheads, ivillage igovernments, iRegency/City i(Provincial) igovernments, ifrom Bank iIndonesia iin idevelopment iof iSMEs, ifrom ithe iDepartment iof iAgriculture i(assistance ifor agricultural ibusinesses iand iprovision iof iagricultural iproduction iequipment iand itransfer iof agricultural itechniques iand itechnology), ifrom ithe iUniversity iof iTanjungpura i(transfer iof knowledge iand itechnology).